The Functionally Characterization of Putative Genes Involved in the Formation of Mannose in the Aplanospore Cell Wall of Haematococcus pluvialis (Volvocales, Chlorophyta) - Chunli Guo (MDPI AG, 2021)
Unicellular volvocalean green algal Haematococcus pluvialis, known as astaxanthin rich microalgae, transforms into aplanospore stage from the flagellate stage when exposed to the stress environments. However, the mechanism of the formation of aplanospore cell wall, which hinders the extraction of astaxanthin and the genetic manipulation is still unclear. In this study, the cell wall components under salicylic acid and high light stresses were explored, and cellulose was considered the main component in the flagellates, which changed gradually into mannose in the aplanospore stages. During the period, the genes related to the cellulose and mannose metabolisms were identified based on the RNA-seq data, which presented a similar expression pattern. The positive correlations were observed among these studied genes by Pearson Correlation (PC) analysis, indicating the coordination between pathways of cellulose and mannose metabolism. The study firstly explored the formation mechanism of aplanospore cell wall, which might be of scientific significance in the study of H. pluvialis.